Economic and Biological Features of the Holstein Cows Selected in Hungary when Year-Round Stable System - Gennadiy Mikhaylovich, Tunikov; Nina Ivanovna, Morozova; Farrukh Ataullakhovich, Musaev; Vyacheslav Ivanovich, Lebedev; Larisa Vasilyevna, Ivanova; Yuliya Sergeevna, Muravyeva (International Journal of Engineering and Technology, 2018)
The purpose of the work is to study economic and biological features of the Holstein cows selected in Hungary when year-round stable system in conditions of the reconstructed dairy complex. Economic characters of purebred Holstein cows of Hungarian selection were studied (86 animals). The diets of cows were formed using the ASP program. Feeding control was carried out on the biochemical parameters of cows' blood. Hematological parameters of blood: leukocytes, erythrocytes and hemoglobin were determined with hematology analyzer XT-2000i from Sysmex. Total protein in blood serum (by biuret reaction), albumins and globulins, and bilirubin were determined with photocolorimeter KFK-2. The content of glucose and cholesterol in the blood was determined with the help of a biochemical automatic analyzer. Blood enzymes: ALT and AST were determined by the Reitman-Fraenkel method. Lactation yield and milk quality of cows were studied by the first three lactations, depending on the genealogical affiliation on three lines: Montvik Chiftain - 17 heads; Vis Beck Idiala - 50 heads and Reflection of Sovering - 19 heads. To study the lactation performance of cows, information recorded in computer base â€œSELEXâ€, functioning at the farm, was used. The intensity of milk ejection was considered with the help of â€œDairymasterâ€ program. The physical-chemical parameters of Holstein cows' milk were studied in the second lactation. The following parameters were determined in milk: density, acidity, freezing point, heat resistance, purity, fat weight fraction, protein, lactose and SOMO. Milk quality parameters were determined with the help of ultrasonic device "Ecomilk-M". In addition to the above parameters, the presence of antibiotics and the number of somatic cells were determined in the commercial milk. Holstein cows of the Hungarian selection had economic and biological features due to age and genealogical affiliation. The maximum milk yield for three full lactations was obtained from cows of the Vis Beck Idiala line - 20,881 kg of milk. In comfortable conditions of keeping and feeding, the Holstein cattle of the Hungarian selection realized the genetic potential: in terms of milk yield by 86.1-98.6 %, in the fat weight fraction by 102.7-108.4 % and in protein weight fraction by 95.2-104.9 %.Â Â